Building regions: a resource-based view of a policy-led knowledge exchange network. Issue 7 (3rd July 2017) - Larty, Joanne; Jack, Sarah; Lockett, Nigel
ABSTRACT: Building regions: a resource-based view of a policy-led knowledge exchange network. Regional Studies . This study looks to understanding further about how important the choice of intermediary can be in supporting policy-makers in their regional development activities. Drawing on the resource-based view as a framework, it provides new insights into resource combinations underpinning the successful creation and expansion of a regional network for knowledge exchange. Through an in-depth study of a partnership of three intermediaries involved in designing and implementing a regional information and communication technology (ICT) network, the study highlights that policy-makers need to consider not only the organizational resources of intermediaries but also the resources of key individuals from those organizations.